Service quality and attitudinal loyalty: Consumers' perception of two major telecommunication companies in Oman - Rakesh Belwal; Mohannad Amireh (Arab Economic and Business Journal, 2018)
Intense competition and shifting loyalties in the Omani telecommunication sector are forcing companies to focus on service quality for increased customer satisfaction, customer loyalty, and organizational profitability. This study assesses the service quality for two major telecommunication companies - Omantel and Ooredoo - in the Sultanate of Oman using the SERVQUAL model and tests the effect of five SERVQUAL dimensions on the attitudinal loyalty of customers. The analysis of data using the partial least squared (PLS) based Structural Equation Modeling technique reveals a positive effect of reliability and assurance dimensions on attitudinal loyalty. However, the outcomes do not reflect any significant effect of tangibles, responsiveness, and empathy on attitudinal loyalty. The multi-group analysis does not reveal any significant difference between the Ooreedoo and Omantel customers pertaining to the effect of the SERVQUAL dimensions on attitudinal loyalty. Whilst the study reveals the significance of reliability and assurance dimensions in affecting attitudinal loyalty of telecom customers for the long-term profitability, it also indicates the possibility of tangibles, responsiveness, and empathy in affecting behavioral loyalty to prevent customers' switching in the short-run. By positioning their service quality focus on reliability and assurance, telecom companies can secure a higher attitudinal loyalty and profitability in the long term.
Keywords: 650; Telecommunication services; Oman; SERVQUAL; Customer loyalty